Multicenter Case–Control Study of Behavioral, Environmental, and Geographic Risk Factors for Talaromycosis, Vietnam - Lottie Brown; Brian Jonat; Vo Trieu Ly; Nguyen Le Nhu Tung; Pham Si Lam; Nguyen Tat Thanh; Dang Thi Ngoc Bich; Vu Phuong Thao; Nguyen Thi Mai Thu; Ngo Thi Hoa; Thuy Le (Emerging Infectious Diseases)
Talaromycosis is a life-threatening fungal disease that primarily affects immunocompromised persons in Southeast Asia. We conducted a multicenter, case–control study recruiting participants with advanced HIV disease in Vietnam; 205 case-patients with culture-confirmed talaromycosis were matched to 405 control-patients by age, sex, and CD4 count. Occupational exposure to tropical plants (odds ratio [OR] 1.73 [95% CI 1.10–2.73]; p = 0.017) and to farmed animals (OR 2.07 [95% CI 1.20–3.55]; p = 0.009) were independent risk factors for talaromycosis. Talaromycosis risk was higher in participants from highland regions than in persons from lowland regions (p<0.05). Participants from lowland regions who had lived or traveled to highland regions had a higher risk for talaromycosis (OR 3.15 [95% CI 1.49–6.64]; p = 0.003). This study confirms the epidemiologic correlation between talaromycosis and soil exposure and demonstrates an epidemiologic link between talaromycosis and residence in or travel to highland regions of Vietnam.